Social Capital Strengthening Model in the Framework of the Employment Expansion for Native Papuan in Manokwari District, West Papua - Lodewijk L. Wanggai (Annals of Management and Organization Research, 2021)
Purpose: The aim of this study is to seek the framewok model of the employement expansion for indigenous Papuans in West Papua. Method: The approach used is grounded theory based on phenomena by applying in the form of concepts, categories, and propositions as a means of construction, reconstruction, and elaboration in a social process, with a constructivism paradigm model and more emphasis on the emic approach.Methods of observation, interviews, and documentation. Result: The research findings show, namely; (1) there is an imbalance of knowledge and understanding of the meaning of trust; (2) there is a tendency for indigenous Papuans to prefer to work in the formal sector rather than in the informal sector; (3) the collaboration of social capital and other capital in the process of expanding employment opportunities; (4) indigenous Papuans have no mutual trust, mutual suspicion of one another, a sense of inferiority; (5) a sense of injustice (6) the government in empowerment there is no follow-up; (7) MRPB and LMA should collaborate with the Special Autonomy faction, Regional Apparatus, Organizations (OPD), TNI/Polri, and the private sector; (8) Perda and Perdasus constraints Limitations: There may be something wrong with the implementation of special autonomy in terms of expanding employment opportunities for indigenous Papuans, both in the informal and formal sectors. Contribution: The presence of the Special Autonomy Law in Papua and West Papua will be a solution or a problem for indigenous Papuans.